Development of a novel ex vivo porcine skin explant model for the assessment of mature bacterial biofilms. Issue 5 (8th August 2013) - Yang, Qingping; Phillips, Priscilla L.; Sampson, Edith M.; Progulske‐Fox, Ann; Jin, Shouguang; Antonelli, Patrick; Schultz, Gregory S.
Abstract Bacterial biofilms have been proposed to be a major factor contributing to the failure of chronic wounds to heal because of their increased tolerance to antimicrobial agents and the prolonged inflammation they cause. Phenotypic characteristics of bacterial biofilms vary depending on the substratum to which they attach, the nutritional environment, and the microorganisms within the biofilm community. To develop an ex vivo biofilm model that more closely mimics biofilms in chronic skin wounds, we developed an optimal procedure to grow mature biofilms on a central partial‐thickness wound in 12‐mm porcine skin explants. Chlorine gas produced optimal sterilization of explants while preserving histological properties of the epidermis and dermis. Pseudomonas aeruginosa and Staphylococcus aureus developed mature biofilms after 3 days that had dramatically increased tolerance to gentamicin and oxacillin (∼100× and 8, 000× minimal inhibitory concentration, respectively) and to sodium hypochlorite (0.6% active chlorine). Scanning electron microscopy and confocal microscopy verified extensive exopolymeric biofilm structures on the explants. Despite a significant delay, a ΔlasI quorum‐sensing mutant of P. aeruginosa developed biofilm as antibiotic‐tolerant as wild‐type after 3 days. This ex vivo model simulates growth of biofilms on skin wounds and provides an accurate model to assess effects of antimicrobial agents on mature biofilms.